Deformation Structures From Splay and Décollement Faults in the Nankai Accretionary Prism, SW Japan(IODP NanTroSEIZE Expedition 316): Evidence for Slow and Rapid Slip in Fault Rocks. (9th June 2020) - Fabbri, O.; Goldsby, D. L.; Chester, F.; Karpoff, A. M.; Morvan, G.; Ujiie, K.; Yamaguchi, A.; Sakaguchi, A.; Li, C. F.; Kimura, G.; Tsutsumi, A.; Screaton, E.; et al.
Abstract: Drilling during IODP NanTroSEIZE Expedition 316 led to the recovery of cores from the basal décollement in the frontal part of the Nankai accretionary prism and from a splay fault branching from the décollement at 25‐km landward of the prism toe. The core from the splay fault shows a main shear zone and two secondary shear zones. The main shear zone can be divided into two subzones. The upper subzone consists of a 1.2‐mm thick foliated gouge zone truncated downward by a through‐going fault encompassing a 0.4‐mm thick weakly foliated gouge interval. A nearby 200‐μm thick granular injection vein is interpreted as derived from the fault. The lower subzone consists of a foliated clayey gouge. A 70‐μm thick granular injection vein is also observed along this subzone. In the basal décollement core, microstructures consist of foliated gouge along a flat‐lying shear zone and seven flat‐lying or gently dipping secondary or incipient shear zones above. A redox front lies beneath the main shear zone. The shear zone and the redox front are truncated by a fault surface outlined by microbreccia developed at the expense of the overlying foliated gouge. Foliated gouge from the shear zones is tentatively interpreted as resulting from slow slip or aseismic creep. The weakly foliated gouge, the microbreccia, and the granular injection veins are interpreted as resulting from coseismic slip. The presence of the redox front beneath the main shear zone of the décollement fault core is interpreted as a consequence of oxidizing fluid flow along the microbreccia‐bearing fault. Plain Language Summary: To understand why some large subduction zone earthquakes are followed by destructive tsunamis and others are not is a key issue in seismic hazard assessment. Tsunami genesis is suspected to depend mainly on the capacity of faults in shallow parts of subduction zones to either transfer seismic slip from hypocentral depth upward or to dampen it before it reaches the surface. Expedition 316 of the IODP NanTroSEIZE program drilled across and retrieved cores from two major fault zones in the frontal part of the Nankai accretionary prism off Kii Peninsula. The rocks constituting the cored fault zones show microstructures which testify to both slow slip (plate tectonic steady‐state creep velocity or slow slip transient event velocity) and rapid slip (conventional earthquake slip velocity). It follows that in the Nankai Trough off Kii Peninsula, earthquake rupture can propagate along either of the major faults known there. Key Points: IODP Expedition 316 drilling across two fault zones in the Nankai accretionary prism allowed the recovery of intact cores of fault rocks Fault rocks consist of microbreccia and weakly foliated gouge along sharp planar fault surfaces and foliated clayey gouge in millimeter‐thick shear zones Microbreccia and weakly foliated gouge suggest propagation of seismic slip along fault surfaces, while foliated gouge suggests aseismic or slow slip along shear zones